Development of Yoga Program for Spiritual Well-Being for Breast Cancer Patients Receiving Chemotherapy - chutiraka, suijntana; Perngmark, Pajongsil; Chukumnerd, Prapaporn (Journal of Research in Nursing-Midwifery and Health Sciences, 2020)
The objective of this study aimed to develop a yoga program to promote spiritual well-being for breast cancer patients receiving chemotherapy. Two phases of program development and program evaluation were conducted. Content validity evaluation was validated by three experts; program feasibility was tested by five professional nurses working in cancer hospital. The program development comprised three components: a program guideline, an activity plan, and yoga handbook (CD and poster for patients’ breast cancer receiving chemotherapy). Content validity was evaluated by three experts reporting that the program was consistent with the objectives and content, but should adjust the item question (in some queries) to change into easy wording and clear meaning. The feasibility of the program was tested suitable for its use. Some suggestions were mentioned: 1) Besides distribution CD clip of Yoga practice, it should be distributed via social media such as youtube to get better more convenience and accessible; 2) The training place should be near to the chemotherapy unit; and 3) Training period should incorporate to practice while waiting for the blood test results, in order to reduce patient’s anxiety from waiting for examination queue calling. In conclusion, professional nurses and healthcare workers could use the new Yoga program to enhance better spiritual wellbeing of breast cancer patients receiving chemotherapy